Women, War, and the Making of Bangladesh : Remembering 1971 - Saikia, Yasmin (Book collections on Project MUSE., 2011)
The war of 1971, fought between India and what was then East and West Pakistan, led to the creation of Bangladesh, where it is remembered as the War of Liberation. For India, the war represents a triumphant settling of scores with Pakistan. If the war is acknowledged in Pakistan, it is cast as an act of betrayal by the Bengalis. None of these nationalist histories conveys the human cost of the war. Pakistani and Indian soldiers and Bengali militiamen raped and tortured women on a mass scale. In Women, War, and the Making of Bangladesh survivors tell their stories, revealing the power of speaking that deemed unspeakable. They talk of victimizationoof rape, loss of status and citizenship, and "war babies" born after 1971. The women also speak as agents of change, as social workers, caregivers, and wartime fighters. In the conclusion, men who terrorized women during the war recollect their wartime brutality and their post-war efforts to achieve a sense of humanity. Women, War, and the Making of Bangladesh sheds new light on the relationship between nation, history, and gender in postcolonial South Asia.